EMPLOYMENT OF GRADUATES OF KAZAKHSTAN UNIVERSITIES: ANALYSIS OF PROBLEMS - Francesco, Agnati Luigi; Minazheva, G. S.; Sadyrova, M. S.; Shakhmatova, N. V. (Farabi Journal of Social Sciences, 2020)
The article is devoted to the analysis of the employment of graduates of Kazakhstan universities and the identification of existing problems. The purpose of this article is to provide an overview of some dominant empirical and conceptual topics in the field of employment of graduates of Kazakhstan universities. Global trends in higher education, the transition to a European educational model are making changes in the employment system of graduates of Kazakhstan’s universities. The article identifies the main contradictions in the employment of graduates, on the basis of a sociological study among graduates the main factors are shown that contribute to solving the problem of effective employment of graduates. In this regard, it is considered advisable to implement the concept of interaction between the educational system and the labor market, which would ensure the saturation of the economy with qualified personnel. The traditional human and cultural capital that employers have always demanded is currently only part of the narrative of graduate employment. The employment opportunity of graduates should increasingly be embodied in their so-called personal capital, which entails the integration of academic abilities with personal, interpersonal and behavioral qualities.